DER UMGANG MIT FREMDEM UND FREMDHEIT - Abdunazarov Feruz Kuchkorovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
It is better to have a relationship with strangers and people who are not strangers. Interacting with strangers is one of the most important aspects of demonstrating intercultural competence. The question of what is meant by "conformity" in this article, and what is meant by "foreignness" and "foreignness" can be found in this article.